2022
DOI: 10.54783/jin.v4i2.546
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kemauan Membayar (Willingness to Pay) Iuran Jaminan Kesehatan Nasional Pada Peserta Mandiri Di Kota Jambi Tahun 2021

Abstract: This study aims to determine the determinants of willingness to pay national health insurance contributions to independent participants in Jambi City. This study uses a quantitative method with a cross sectional design. The population is all participants of the National Health Insurance (JKN) in 3 sub-districts (East Jambi District, Jambi Market and Jelutung) namely 42,592 participants. The sampling technique used was purposive sampling. The results of this study indicate that there is a relationship between, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…This result aligns with a study conducted by Apriani (2021), which states that the determinants of willingness to pay JKN premiums include the ability to pay premiums, including income, expenditures, and family size. These findings also correspond with the findings of Istamayu et al (2022), which suggest a relationship between the ability to pay premiums and the willingness to pay, indicating that higher income influences individuals to become JKN participants and determines their willingness to pay JKN premiums. Individuals with higher income who are willing to pay believe that health is a crucial primary need, and therefore, they see the need for insurance that can be used in case of illness (Istamayu et al, 2022).…”
Section: Resultssupporting
confidence: 87%
“…This result aligns with a study conducted by Apriani (2021), which states that the determinants of willingness to pay JKN premiums include the ability to pay premiums, including income, expenditures, and family size. These findings also correspond with the findings of Istamayu et al (2022), which suggest a relationship between the ability to pay premiums and the willingness to pay, indicating that higher income influences individuals to become JKN participants and determines their willingness to pay JKN premiums. Individuals with higher income who are willing to pay believe that health is a crucial primary need, and therefore, they see the need for insurance that can be used in case of illness (Istamayu et al, 2022).…”
Section: Resultssupporting
confidence: 87%
“…Apart from other influencing factors such as knowledge (Marzuki et al, 2019;Rohmawati, 2014) and perceptions of the quality of health services (Hildayanti et al, 2021), which were not examined in this study, the results of this study are thought to be caused by the uncertainty in economic conditions, especially during the pandemic era. The increased contribution rates while the economic situation was uncertain will make respondents unwilling to pay more for the JKN membership fee, as shown in the previous study in Jambi City (Istamayu et al, 2022), which showed that income is a determinant factor for the WTP with a p-value of 0,000 (<0,05), especially given the different economic situations faced by the community during and after the pandemic. It can be seen that the majority of respondents objected to an increase in the scenario of increasing JKN contribution rates.…”
Section: Wtp For Jkn Membership Feementioning
confidence: 97%
“…The income received by people certainly differs from one to another, this is due to the different types of work they do. 9,23 Based on the research results, it shows that the majority of independent BPJS Health participants in the Bua Health Center working area, Luwu Regency, who have high income categories, are willing to pay BPJS Health contributions. Meanwhile, the majority of independent BPJS Health participants in the Bua Health Center working area, Luwu Regency, who have low income categories, are not willing to pay BPJS Health contributions.…”
Section: The Influence Of Number Of Family Members On Willingness To ...mentioning
confidence: 99%
“…The willingness to pay national health insurance contributions according to the time specified for independent participants is the most important component in the health financing system. 9 Based on data from Palopo City BPJS Health in 2022, 74.933 people were registered as independent BPJS Health participants in Luwu Regency. The number of independent BPJS Health participants in Luwu Regency who are in arrears in payment of contributions is based on participant class, namely class 3 as many as 20.956 people, class 2 as many as 4.691 people and class 1 as many as 2.649 people.…”
Section: Introductionmentioning
confidence: 99%